Development of Interactive Learning Media Using Android-based Google Sites to Increase Students' Interest in Learning - Arif Rifa’i; Muchyidin, Arif; Indah Nursuprianah (MASI Mandiri Edukasi, 2024)
In this study, researchers found a problem: there is still a lack of student interest in learning mathematics due to the media provided, which is less innovative and interactive, so students feel bored. Therefore, this research aims to (1) develop interactive learning media using Google Sites based on Android to increase student learning interest in Flat Buildings material grade VII SMP / MTs, (2) test the feasibility of the media, and (3) increase student learning interest. The research method used is Research and Development (R&D) with the 4-D development model (Define, Design, Development, Disseminate). The instruments used were expert validation, student response, learning interest, and pretest-posttest questionnaires. The results of this study obtained an average value from media experts of 92% with a very feasible category, while material experts obtained an average of 84% with a feasible category. The results of the N-Gain test obtained an average value of 82%, and the results of the student interest questionnaire of 76.62%. These results show that Android-based Google Sites learning media effectively increases student interest in learning. It can be concluded that interactive learning media using Android-based Google Sites is feasible and effective in increasing student interest in learning.